Emergent Median Sternotomy for Mediastinal Hematoma: A Rare Complication following Internal Jugular Vein Catheterization for Chemoport Insertion—A Case Report and Review of Relevant Literature. (30th January 2014) - Biswas, Saptarshi; Sidani, Marwa; Abrol, Sunil
Abstract : Mediastinal hematoma is a rare complication following insertion of a central venous catheter with only few cases reported in the English literature. We report a case of a 71-year-old female who was admitted for elective chemoport placement. USG guided right internal jugular access was attempted using the Seldinger technique. Resistance was met while threading the guidewire. USG showed a chronic clot burden in the RIJ. A microvascular access was established under fluoroscopic guidance. Rest of the procedure was completed without any further issues. Following extubation, the patient complained of right-sided chest pain radiating to the back. Chest X-ray revealed a contained white out in the right upper lung field. She became hemodynamically unstable. Repeated X-ray showed progression of the hematoma. Median Sternotomy showed posterior mediastinal hematoma tracking into right pleural cavity. Active bleeding from the puncture site at RIJ-SCL junction was repaired. Patient had an uneventful recovery. Injury to the central venous system is the result of either penetrating trauma or iatrogenic causes as in our case. A possible explanation of our complication may be attributed to the forced manipulation of the dilator or guidewire against resistance. Clavicle and sternum offer bony protection to the underlying vital venous structures and injuries often need sternotomy with or without neck extension. Division of the clavicle and disarticulation of the sternoclavicular joint may be required for optimum exposure. Meticulous surgical technique, knowledge of the possible complications, and close monitoring in the postprocedural period are of utmost importance. Chest X-ray showed to be routinely done to detect any complication early.